Correction: Improving the impact of HIV pre-exposure prophylaxis implementation in small urban centers among men who have sex with men: An agent-based modelling study. - Jason R Gantenberg; Maximilian King; Madeline C Montgomery; Omar Galárraga; Mattia Prosperi; Philip A Chan; Brandon D L Marshall (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0199915.].